THE IMPLEMENTATION OF MEDICAL TOURISM IN INDONESIA - Suadi Sapta Putra; Elwisam; Kumba Digdowiseiso; Nguyen Duc Tri; Nurul Nazwa Napatah (RADJA PUBLIKA, 2024)
The government and health industry in Indonesia must consider the dynamic foundation created by the opportunities and challenges in the global Medical Tourism market. The objective of this study is to assess the progress and scope of Medical Tourism in Indonesia by analyzing existing literature, as well as identifying the key factors that contribute to its effectiveness in attracting medical tourists. The employed methodology is qualitative as it allows for a comprehensive understanding of the intricacies and intricacies involved in the implementation of Medical Tourism. The research findings indicate that the government plays a crucial role in maximizing the potential of Medical Tourism in Indonesia. This is achieved through the implementation of incentive policies and effective promotions. Enhancing regulatory measures, elevating health service benchmarks, and fostering collaboration among stakeholders in the health and tourism industries are crucial measures to enhance Indonesia's appeal as a Medical Tourism hub.